2007
DOI: 10.1590/s0102-76382007000400017
|View full text |Cite
|
Sign up to set email alerts
|

Troca valvar mitral minimamente invasiva videoassistida

Abstract: The use of minimally invasive technics in cardiac surgery has become widely discussed, aiming improvements not only in the aesthetics aspects but also better functional results. In this report, we present a case of a patient with severe mitral stenosis that underwent successful video-assisted minimally invasive mitral valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Some studies [10][11][12][13][14][15] have demonstrated that, in video-assisted surgeries, incisions can be smaller, visualization of the surgical field is improved, and long-term results are the same as those of conventional mitral valve surgery. Furthermore, there is substantial reduction in trauma, mechanical ventilation as well as hospital stay, so the patient can return to routine activities faster than in conventional surgeries, where the patient cannot drive for 45 days as opposed to 10 to 15 days in minimally invasive surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [10][11][12][13][14][15] have demonstrated that, in video-assisted surgeries, incisions can be smaller, visualization of the surgical field is improved, and long-term results are the same as those of conventional mitral valve surgery. Furthermore, there is substantial reduction in trauma, mechanical ventilation as well as hospital stay, so the patient can return to routine activities faster than in conventional surgeries, where the patient cannot drive for 45 days as opposed to 10 to 15 days in minimally invasive surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of videothoracoscopy, there was the possibility of ever smaller incisions or absence of them [19]. There are several factors that make this technique still unusual in our country [2].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach depended on the pathology approached. In the case of mitral valve disease, videoassisted right anterolateral minithoracotomy was performed [2] (Figure 1) at an early stage and later the periareolar technique was adopted [3] (Figure 2). Patients were intubated using Carlens orotracheal tube for selective ventilation, and positioned with the right side of the chest occlusion was achieved through the use of Endoclamp (Estech Inc.) introduced via the femoral artery.…”
Section: Methodsmentioning
confidence: 99%
“…We believe that the open mitral commissurotomy has advantages over the valvuloplasty balloon catheter [22,23], with lower incidence of postoperative complications and clinical outcomes consistent long-term, and the adoption of minimally invasive techniques [24,25], we can further improve these results and provide a treatment of the mitral valve with quality and aesthetic benefits.…”
Section: Ipo = Immediate Post-operativementioning
confidence: 99%